Back Cover: Magnetoelectric oxide films for spin manipulation in graphene (Phys. Status Solidi RRL 3/2016). Issue 3 (March 2016) - Stuart, S. C.; Gray, B.; Nevola, D.; Su, L.; Sachet, E.; Ulrich, M.; Dougherty, D. B.
Abstract : No abstract is available for this article. Abstract : In their Letter (pp.242–247 ), Stuart et al. describe a materials science advance in the quest to develop graphene spintronics. The authors report on the growth and characterization of simple magnetoelectric oxide films of chromia (Cr2 O3 ) on graphene and graphite substrates that are a pre‐requisite to create a graphene spin field effect transistor. In this device, spin precession in a channel is hypothesized to be controllable by direct exchange interactions with the magnetization of the gate (schematically indicated in the cover graphic). Despite only modest crystallinity in the chromia gate films, Stuart et al. find that careful magnetoelectric annealing results in surfaces with the kind of spontaneous boundary magnetization that is well‐known for this unique oxide. Moreover, they demonstrate the critical ability to control the boundary magnetization with a continuously tunable electrostatic field by local contact mode writing with an electrically biased AFM tip. These observations suggest that if chromia films can be integrated with graphene spin transport channels, an exchange‐based graphene spin transistor is within reach.